The importance of the membrane for biophysical measurements - Chorev, DS; Robinson, CV (Springer Nature, 2020)
Within cell membranes numerous protein assemblies reside. Among their many functions, these assemblies regulate the movement of molecules between membranes, facilitate signaling into and out of cells, allow movement of cells by cell-matrix attachment, and regulate the electric potential of the membrane. With such critical roles, membrane protein complexes are of considerable interest for human health, yet they pose an enduring challenge for structural biologists because it is difficult to study these protein structures at atomic resolution in in situ environments. To advance structural and functional insights for these protein assemblies, membrane mimetics are typically employed to recapitulate some of the physical and chemical properties of the lipid bilayer membrane. However, extraction from native membranes can sometimes change the structure and lipid-binding properties of these complexes, leading to conflicting results and fueling a drive to study complexes directly from native membranes. Here we consider the co-development of membrane mimetics with technological breakthroughs in both cryo-electron microscopy (cryo-EM) and native mass spectrometry (nMS). Together, these developments are leading to a plethora of high-resolution protein structures, as well as new knowledge of their lipid interactions, from different membrane-like environments.